Analisis Yuridis Pasal 49 KUHP terkait Pembelaan Terpaksa dalam Studi Putusan Nomor 115/Pid.B/2021/PN Stb - Siti Nur Ulyatin Zumaroh; Emmilia Rusdiana (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to examine the juridical application of Article 49 KUHP through an analysis of Decision Number 115/Pid.B/2021/PN Stb, with particular attention to the judicial assessment of the elements of self-defense. This research employs normative legal research (doctrinal legal research) using a qualitative approach, supported by the statute approach, case approach, and conceptual approach. The primary legal materials consist of statutory regulations and court decisions, while secondary materials include legal doctrines and scholarly publications in criminal law. The findings reveal that the court’s legal reasoning has not fully accommodated the principles of proportionality and contextual interpretation, resulting in an emphasis on formal legal requirements rather than the protective function of self-defense as a justification ground (rechtvaardigingsgrond). This study concludes that a more contextual and proportional interpretation of Article 49 KUHP is necessary to ensure legal certainty, justice, and legal utility in the application of self-defense provisions.